Kajian Akar Kadaka sebagai Media Tanam dengan Pengaruh Variasi Konsentrasi Indole Butyric Acid Tterhadap Pertumbuhan Anggrek Dendrobium canaliculatum: Study of Kadaka Roots as a Plant Media with the Effect of Variation Concentrations of Indole Butyric Acid on Dendrobium canaliculatum Orchid Growth - Hadi, Muhammad Sholikhul; Rahayu, Tintrim; Jayanti, Gatra Ervi; Agisimanto, Dita (Jurnal SAINS ALAMI (Known Nature), 2023)
Dendrobium is an orchid that many orchid lovers like. Efforts to increase the quantity of orchids in the growth phase can be done in several ways, namely through the regulation of fertilization and the use of appropriate planting media. Planting media from kadaka roots is the right media for the growth of orchid. The addition of nutrients N, P, and K together showed a significant increase in total biomass. In addition to fertilizers, growth regulators substances also affect growth. The plant hormone used in plant cultivation is the auxin hormone. One type of auxin hormone type is Indole Butyric Acid (IBA) which functions to stimulate root formation. This study aimed to study the effect of IBA concentration on the root growth of Dendrobium orchids grown on kadaka root media. Dendrobium orchids seedlings were selected beforehand, planted in kadaka roots, and treated twice a week. The treatment was carried out for two months using IBA concentrations of 0.25, 0.50, 0.75, and 1.0 ml/L. The administration of IBA hormone on the growth of Dendrobium canaliculatum affects the number of new roots, leaf length, and plant height. IBA at 0.25 ml/L was the optimal concentration for the number of new roots. The number of new roots as an indicator of optimal orchid growth in response to IBA hormone administration.  Keywords: Kadaka, Indole Butyric Acid (IBA), Orchid, Orchid Growth   ABSTRAK Dendrobium adalah anggrek yang banyak disukai pecinta anggrek. Upaya peningkatan kuantitas anggrek pada fase pertumbuhan dapat dilakukan dengan beberapa cara yaitu melalui pengaturan pemupukan serta penggunaan media tanam yang sesuai. Media tanam dari akar kadaka merupakan media yang tepat untuk pertumbuhan anggrek. Penambahan unsur hara N, P, dan K pada media secara bersama menunjukkan peningkatan total biomassa yang signifikan. Selain pupuk, Zat Pengatur Tumbuh (ZPT) juga berpengaruh terhadap pertumbuhan. Hormon tanaman yang dipergunakan pada pembudidayaan tanaman adalah hormon auksin. Salah satu jenis hormon auksin merupakan Indole Butyric Acid (IBA) yang dipergunakan untuk merangsang pembentukan akar. Penelitian ini bertujuan untuk mengkaji efek konsentrasi IBA terhadap pertumbuhan akar anggrek Dendrobium yang ditanam pada media akar kadaka. Tanaman anggrek yang digunakan adalah seedling Dendrodium, dilakukan seleksi, ditanam di akar kadaka, dan diberi perlakuan dua kali seminggu. Perlakuan dilakukan selama dua bulan menggunakan konsentrasi IBA 0,25, 0,50, 0,75, dan 1,0 ml/L. Pemberian hormon IBA terhadap pertumbuhan anggrek Dendrobium canalicullatum berpengaruh pada jumlah akar baru, panjang daun dan tinggi tanaman. IBA pada 0,25 ml/L merupakan konsentrasi yang optimal untuk jumlah akar baru. Jumlah akar baru sebagai indikator pertumbuhan anggrek yang optimal terhadap respon pemberian hormon IBA.  Kata kunci: Kadaka, Indole Butyric Acid (IBA), Anggrek, Pertumbuhan